Postural hygiene: factors that influence correct posture in children and adolescents. A systematic review - Nanjarí Miranda, Rodrigo.; Aranda Bustamante, Felipe.; Saavedra León, Valerie.; Zúñiga Vivanco, Janis.; Castillo Paredes, Antonio Jonathan.; Yáñez Sepúlveda, Rodrigo.; Olivares Arancibia, Jorge Eduardo. (Federación Española de Docentes de Educación Física, 2024)
Postural hygiene is the technique of positioning the body in a natural way, whether in a static or dynamic state. In this sense, the spinal column is the base structure for the stability of the human being, therefore, preventive measures must be taken for its correct functioning. The objective of this review is to identify the factors that influence correct body posture in schoolchildren. A search for scientific studies published up to June 2021 was carried out using the PubMed, Web of Science, Scopus and SciELO databases. The keywords used were “body posture” AND children OR adolescents OR schoolchildren OR schoolchildren´s AND school OR schools. All the articles that evaluated the body posture and the effect generated by the habitual use of the backpack in schoolchildren were included. The search strategy yielded 3,030 studies of which 33 met the eligibility criteria. It is necessary to evaluate the changes that are developing in the spine, as well as the creation of exercise programs to prevent errors and postural deformities, in order to improve postural hygiene in children.
Higiene postural: factores que influyen en una correcta postura en niños y adolescentes. Una revisión sistemática
Keywords: Backpack effect; Body posture; Niños; Educación física; Postura humana